The Billionaire Boom: Capital as Power and the Distribution of Wealth - Natasha Popcevski (Covid-19 and the Global Political Economy. Crises in the 21st Century, 2022)
During the pandemic, the world's billionaires increased their net worth to unprecedented historical heights. This was an impressive feat for the world's richest, who took to celebrations by launching themselves into outer space, hosted factory mega-raves, and perhaps more prudently sailed away from the virus on their mega-yachts during the mass suffering caused by the global health crisis. Whether billionaires have profited during the pandemic, or whether billionaires have profited from the pandemic may be difficult to detect with any certainty. However, we know that the accumulation of billionaire wealth has transcended previous orders of magnitude set before the crisis. In this chapter, I use the capital as power framework to argue that ownership and exclusion (institutional power) rather than individual productivity or the exploitation of workers can help us account for the rise of the billionaire class and its increase in wealth throughout the pandemic. However, although ownership and exclusion are key factors in the rapid accumulation of wealth, so too have the unprecedented fiscal stimulus and loose monetary policy of governments and central banks during the pandemic. At least in the United States, there is some survey evidence to suggest that a considerable amount of stimulus checks given by the Biden administration ended up in financial markets, boosting share prices, and thus the wealth of billionaire shareholders like Elon Musk of Tesla. This chapter considers two additional main factors: The turn to neoliberalism and rapid technological change. To demonstrate my argument, I have divided this chapter in the following manner. First, I consider the rise of the billionaire class before and during the pandemic. Second, I consider the neoclassical and Marxist understandings of the distribution of wealth and contrast this with the capital as a power perspective before discussing some of the reasons for the rise in billionaire wealth. In the third section, I briefly consider whether billionaires should exist and canvass some recent proposals to address the divide between billionaires and the vast majority of citizens. The chapter then ends with a short conclusion.
Keywords: P; P1; P12; D3; 330; billionaires; capital as power; dominant capital; income distribution